A personal perception of preaching about God the Creator over time - de Camargo Vieira, Ruy Carlos (2013)
The following article reveals the researcher's perception of the concept of God as creator in the light of the biblical writings also discusses the personal impact that caused this in the life of the researcher, similarly summarizes the concept and perception of God as creator in ancient history, in the beginning of Christianity, and the perception of this concept in the "last days", all of which contrasted with the evolutionary worldview.